The independent influences of heat strain and dehydration upon cognition - van Den Heuvel, A. M.; Haberley, B. J.; Hoyle, D. J.; Taylor, N. A.; Croft, R. J. (European Journal of Applied Physiology, 2017)
Purpose: Many researchers have addressed the potential effects of hyperthermia and dehydration on cognition, often revealing contradictory outcomes. A possible reason for this inconsistency is that experiments may have been inadequately designed for such effects. In this study, the impact of hyperthermia, dehydration and their combination on cognition were evaluated in eight young males, after accounting for a range of experimental limitations. Methods: Passive heating and thermal clamping at two mean body temperatures (36.5, 38.5 °C) were performed under three hydration states (euhydrated, 3 and 5% dehydrated) to assess their effects on difficulty-matched working memory and visual perception tasks, and on a difficulty manipulated perceptual task. Data were analysed according to signal detection theory to isolate changes in response sensitivity, bias and speed. Results: Neither moderate hyperthermia (P = 0.141) nor dehydration (P > 0.604) modified response sensitivity, nor did they significantly interact (P > 0.698). Therefore, the ability to distinguish correct from incorrect responses was unaffected. Nevertheless, hyperthermia, but not dehydration (P = 0.301), reduced the response bias (-0.08 versus 2.2 [normothermia]; P = 0.010) and reaction time (mean reduction 49 ms; P < 0.001), eliciting more liberal and faster responses (P = 0.010). Response bias was reduced for the memory relative to the perceptual task (P = 0.037), and this effect was enhanced during hyperthermia (P = 0.031). Conclusions: These observations imply that, once potentially confounding influences were controlled, moderate hyperthermia, significant dehydration and their combined effects had insufficient impact to impair cognition within the memory and perceptual domains tested. Nonetheless, moderate hyperthermia elicited more liberal and rapid responses.